2022
DOI: 10.1007/s00586-022-07421-6
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of postoperative symptomatic spinal epidural hematoma requiring surgical evacuation: a systematic review and meta-analysis

Abstract: Purpose This systematic review and meta-analysis aimed to determine the incidence of symptomatic spinal epidural hematoma (SSEH) following spine surgery. Methods We systematically searched for all relevant articles that mentioned the incidence of SSEH following the spine surgery published in the PubMed, Embase, and Cochrane Library databases through March 2022 and manually searched the reference lists of included studies. The Newcastle–Ottawa quality asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 66 publications
0
29
0
Order By: Relevance
“…However, when compression lasted for 6 h or more, there was no recovery of neurological function, and progressive necrosis of the spinal cord occurred. Numerous studies have established that rapid evacuation resulted in superior outcomes in neurologic recovery 23,24 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when compression lasted for 6 h or more, there was no recovery of neurological function, and progressive necrosis of the spinal cord occurred. Numerous studies have established that rapid evacuation resulted in superior outcomes in neurologic recovery 23,24 …”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have established that rapid evacuation resulted in superior outcomes in neurologic recovery. 23,24 Therefore, when an epidural hematoma is identified and symptoms such as sensory and muscle weakness worsen, we propose an early intervention to remove the hematoma. Regarding the surgical approach, the hematoma was initially removed through the quadrant channel for a wide vision and ease of removal.…”
Section: Management Strategiesmentioning
confidence: 99%
“…[2,6,17] Major predisposing factors for pSEH included; perioperative/postoperative coagulation disorders, multilevel spinal surgery, prior spine surgery, and intraoperative cerebrospinal fluid leaks (CSF) [Tables 1 and 3]. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] The times to onset of symptomatic postoperative pSEH following all-level spine surgery ranged from an average of 2.7 postoperative hours, [1] to less than 24, [2] to between 24-48 postoperative hrs. [5] [Tables 1-4].…”
Section: Introductionmentioning
confidence: 99%
“…[4] The most critical factors to limit/avert permanent neurological sequelae of pSEH included; early recognition of new postoperative neurological deficits, obtaining immediate magnetic resonance imaging (MR) studies, and performing emergency spine surgery where indicated [Tables 1-4]. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Incidence of pSEH e incidence of symptomatic postoperative spinal epidural hematomas (pSEH) involving all spinal levels ranged in 7 studies from 0.1% to 1%, [1,2,4,8,9,15,16] in 5 series from <1% to 2.9%, [11,12,15,17,18] and in 3 series between 3%-4.46% (i.e., the 1 of 10 patients with a 10% incidence of pSEH was considered an outlier) [2,6,17] [Tables 1 and 2]. [1][2][3][4][5][6][7][8][9][10]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation